Multislice computed tomography/contrast-enhanced ultrasound image fusion as a tool for evaluating unclear renal cysts - Rübenthaler, Johannes (Ultrasonography, 2019)
Ultrasonography is a generally accepted imaging technique for diagnosing and monitoring cystic renal lesions. The widely used Bosniak classification (I-IV) categorizes renal cystic lesions into five distinctive groups according to ultrasonography and computed tomography (CT) image criteria. For solid renal lesions, determination of vascularity is discriminatory for malignancy in most instances. In indeterminate cases, contrast-enhanced ultrasound (CEUS) and magnetic resonance imaging/CT-ultrasound image fusion are able to detect and characterize difficult pathologies, with superior performance to either technique alone. In contrast to multislice CT (MS-CT), ultrasound image fusion is a real-time imaging technique that can be used in combination with other cross-sectional imaging modalities. This technical note describes state-of-the-art image fusion of CEUS and MS-CT to detect and characterize unclear renal pathologies.